Mayhall's Hospital epidemiology and infection prevention - Weber, David J. (David Jay), 1951-; Talbot, Thomas R. (Wolters Kluwer, 2021)
"The fifth edition of Mayhall's Hospital Epidemiology and Infection Prevention has a new streamlined focus, with new editors and contributors, a new two-color format, and a new title. Continuing the legacy of excellence established by Dr. C. Glen Mayhall, this thoroughly revised text covers all aspects of healthcare-associated infections and their prevention and remains the most comprehensive reference available in this complex field. It examines every type of healthcare-associated (nosocomial) infection and addresses every issue relating to surveillance, prevention, and control of these infections in patients and in healthcare personnel, providing unparalleled coverage for hospital epidemiologists and infectious disease specialists"--